(untitled) (Pravaha, 2024)
This study analyzes how board independence influences financial performance and operational efficiency in Nepalese commercial banks, focusing on governance practices, strategic decision-making, and regulatory compliance. A mixed-methods design was used, combining quantitative analysis of financial data from Nepalese banks with qualitative insights from interviews with industry experts. Metrics like ROA, ROE, and cost-to-income ratios assessed the impact of board independence. Greater board independence is positively correlated with improved financial performance and operational efficiency. Banks with more independent boards showed better ROA, ROE, and cost-to-income ratios, along with enhanced governance quality. Board independence is crucial for enhancing the performance of Nepalese banks, contributing to better governance, financial metrics, and decision-making. Optimizing board structures can improve governance outcomes in emerging markets. This study expands the limited literature on board independence in Nepalese banks, providing both quantitative and qualitative insights. It offers practical implications for policymakers to optimize board composition for better performance.